1997
DOI: 10.1073/pnas.94.6.2699
|View full text |Cite
|
Sign up to set email alerts
|

In vivo 13 C NMR measurements of cerebral glutamine synthesis as evidence for glutamate–glutamine cycling

Abstract: The cerebral tricarboxylic acid (TCA) cycle rate and the rate of glutamine synthesis were measured in rats in vivo under normal physiological and hyperammonemic conditions using 13 C NMR spectroscopy. In the hyperammonemic animals, blood ammonia levels were raised from control values of Ϸ0.05 mM to Ϸ0.35 mM by an intravenous ammonium acetate infusion. Once a steady-state of cerebral metabolites was established, a [1-13 C]glucose infusion was initiated, and 13 C NMR spectra acquired continuously on a 7-tesla sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
349
3
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(369 citation statements)
references
References 36 publications
15
349
3
2
Order By: Relevance
“…The high oxidative activity seems to support this interpretation, but its further investigation requires a kinetic model. Whereas extensive studies of the glutamate-glutamine cycle (Shen et al, 1999) and measurements of glutamine flux from astrocytes to neurons in glutamatergic transmission (Sibson et al, 1997;Su et al, 1997) have been reported, in GABAergic neurotransmission, the difficulty in separating relative contributions of exogenous glutamate and glutamine to GABA synthesis has resulted in large differences in the quantification of the GABA-glutamine flux: a very small glutamine flux from astrocytes to GABAergic neurons, recently reported by Yang et al (2007), emphasized a lower contribution of glutamine to GABA synthesis than previously hypothesized, which is qualitatively in line with our findings. The present model comprises the astrocyte and GABAergic neuron only, and the omission of the glutamatergic neuron compartment is being taken into account only by reducing the availability of substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high oxidative activity seems to support this interpretation, but its further investigation requires a kinetic model. Whereas extensive studies of the glutamate-glutamine cycle (Shen et al, 1999) and measurements of glutamine flux from astrocytes to neurons in glutamatergic transmission (Sibson et al, 1997;Su et al, 1997) have been reported, in GABAergic neurotransmission, the difficulty in separating relative contributions of exogenous glutamate and glutamine to GABA synthesis has resulted in large differences in the quantification of the GABA-glutamine flux: a very small glutamine flux from astrocytes to GABAergic neurons, recently reported by Yang et al (2007), emphasized a lower contribution of glutamine to GABA synthesis than previously hypothesized, which is qualitatively in line with our findings. The present model comprises the astrocyte and GABAergic neuron only, and the omission of the glutamatergic neuron compartment is being taken into account only by reducing the availability of substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Exogeneous glutamine, formed in astrocytes through the astrocyte-specific enzyme glutamine synthetase, is the most prominent candidate for GABA precursor. In the context of energetics of excitation, glutamine is generally accepted as a metabolic precursor for glutamate synthesis in glutamatergic neurons in which its influx from astrocytes has been experimentally identified and quantified (Sibson et al, 1997;Shen et al, 1999). In GABAergic neurons, in which the machinery for synthesis of GABA from glutamine is more complex and may vary across the different populations of GABAergic neurons (Waagepetersen et al, 1998), the role of glutamine is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…42 Of note, in vivo 13 C MRS studies suggest that the rate of the tricarboxylic acid cycle is not significantly altered during ammonia infusion. 43 The anesthetized model of FHF, first described by Sielaff et al, 14 was used in this study. This dog model provided a large brain for intraventricular catheter placement and MRS data acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Using mass balance analysis Sibson and coworkers 29,30 showed that the only net flux from astrocytic pyruvate dehydrogenase into glutamine is via anaplerosis, which is also localized to the glia. A schematic of the glutamate/glutamine cycle (see text for description).…”
Section: Mrs Studies Of Neuronal Glial Gluta-mate Traffickingmentioning
confidence: 99%
“…18,27 However the rate of the glutamate/glutamine cycle was not uniquely determined from these first experiments due to the inability to distinguish the glutamate/glutamine cycle from other sources of glutamine labeling in the glia. The studies in rats by Sibson and coworkers 29,30 allowed a constraint to be placed on the maximum flow of label from glial pyruvate dehydrogenase into glutamine as the rate of anaplerosis. Using this constraint in the isotopic analysis, Shen and colleagues 33 were able to assess whether a high level of glutamatergic activity is present Figure 2.…”
Section: Mrs Studies Of Neuronal Glial Gluta-mate Traffickingmentioning
confidence: 99%